A study of the impact of ICT on banking activities in Ghana (A case study of selected banks in Ghana) - Kwateng, Kwame Owusu (2012)
A dissertation submitted to the-Institute in partial fulfilment of the requirements for the degree of Master of Science (Information & Communication Management)